Bio-efficacy of Ethanol Based Botanical Extracts against Bipolaris maydis Causing Maydis Leaf Blight in Maize (Zea mays L.) - Piyush; Rakesh Develash; Chetna Mahajan; Tanisha Gupta; Piyush Dogra (Archives of Current Research International, 2025)
Maydis leaf blight of maize caused by Bipolaris maydis has been observed as an alarming problem in maize growing regions leading to significant damage to crop and ultimately reducing grain yield production. This disease is most prevalent under humid and warm maize-growing areas worldwide. The alcoholic leaf extracts of four plants viz., Ageratum conyzoides, Lantana camera, Eucalyptus globulus and Melia azedarach were evaluated at different concentrations for their efficacy against B. maydis under in vitro conditions. Among all extracts, Lantana camera had maximum mycelial inhibition of 100 per cent followed by Eucalyptus globulus having 92.80 per cent of inhibition at 5 per cent test concentration, respectively. Thus, among all test botanicals, Lantana camera was found the most efficient against B. maydis. These findings suggest that Lantana camera extracts could be used as eco-friendly alternatives to control the maydis leaf blight of maize.